Introduction: Multicultural youth vernaculars in Paris and urban France. Issue 2 (31st July 2018) - CHESHIRE, JENNY; GARDNER-CHLOROS, PENELOPE
Abstract : The papers in this Special Issue present some of the results of the Multicultural London English/Multicultural Paris French project, supported by the UK Economic and Social Research Council (ESRC) from October 2010 to December 2014 and by the French Agence Nationale de la Recherche (ANR) from 2010–2012. The project compared language variation and change in multilingual areas of London and Paris, focusing on the language of young people of recent immigrant origin as well as that of young people whose families had lived in London or Paris for many generations. Similar projects in other European cities have documented the emergence of new ways of speaking and rapid language change in the dominant 'host' language, which are attributed to the direct and indirect effects of language contact; see, for example, Wiese2009 on young people's language in Berlin, Quist2008 on youth language in Copenhagen, and Svendsen and Røyneland2008 on Norwegian). In London, young children from diverse linguistic backgrounds tend to acquire English in their peer groups at nursery school rather than from their parents, many of whom do not speak English or are in the early stages of learning English. Since their peers speak a wide range of different languages, the only language the young children have in common is English; and since many of their friends are also acquiring English, there is no clear target model, a high tolerance of linguistic variation, and plenty of scope for linguistic innovation. By the time they reach adolescence, young people's English has stabilized, and many innovations have become part of a new London dialect, now known as Multicultural London English (Cheshire et al., 2013 ). New urban dialects and language practices such as these have been termed 'multiethnolects': they contain a variable repertoire of innovative phonetic, grammatical, and discourse-pragmatic features. In multiethnic peer groups, where local children from many different linguistic backgrounds grow up together, the innovative features are used by speakers of all ethnicities, including those of local descent such as, in London, young monolingual English speakers from Cockney families. Nevertheless they tend to be more frequent in the speech of bilingual young people of recent immigrant origin, and by young speakers with highly multiethnic friendship groups (see further Quist2008 for an account of the use of features associated with a multiethnolect in conjunction with nonlinguistic 'markers' of style, such as tastes in music and preferred ways of dressing). Our project aimed to determine whether a similar outcome had occurred in multicultural areas of Paris.